Οι Έλληνες της Βιθυνίας και το εθνικό κέντρο, 1898-1903: Ανέκδοτες μαρτυρίες από το αρχείο του συλλόγου "Ανατολή" - Κιτρομηλίδη, Μάγδα Μ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1990)
This paper presents and discusses a series of letters addressed between 1898 and 1903 by George Paschalides, a pharmacist at Pera in Constantinople to Margaritis Evangelides, professor at the University of Athens and chairman of the Association of Asia Minor natives in Athens «Anatoli» (Orient). Both correspondents were natives of Bithynia in Northwestern Asia Minor. The letters deal for the most part with the educational needs and difficulties facing two Orthodox Armenian-speaking communities in the region, Ortaköi and Choudi. In requesting the Association’s assistance, Paschalides expresses at the same time the expectations and disappointments of Asia Minor Greeks at the neglect they felt was shown towards them by the Greek consular authorities in Constantinople but also by educational agencies in Athens, especially the Philekpaideftiki Etaireia (Education-promotion Society) whose professed aim had been the encouragement of Greek education among the unredeemed Orthodox populations of the Ottoman Empire. The correspondent points out that the Society had failed to carry out its own programme which had aroused so much hope among education-loving Greeks in Asia Minor. In addition G. Paschalides refers to other obstacles and difficulties facing the intellectual development of the Greeks in Constantinople itself, chief among them being official Ottoman censorship of their newspapers and other publications, which impeded free expression. After the disappointment from the Philekpaideftiki Etaireia and from Greek officials, the hopes of Asia Minor Greeks focused on the Asociation «Anatoli» for the solution of their problems.